Advanced BlackBerry Development - King, Chris (Apress, 2012)
Carrying a BlackBerry used to speak volumes about a person. When you saw someone tapping at that wide keyboard with both thumbs, you could safely assume that the owner was a businessperson, and that their time was so valuable that they couldn’t afford to be out of touch from the office. Today, you can no longer make that assumption. BlackBerry devices are carried by teenagers, surfers, knitters, seemingly everyone. The rest of the world has caught on to what initially attracted people to these phones: BlackBerry devices offer the Internet in a pocket-sized block. Anyone who has experienced that large screen, that expansive keyboard, that powerful processor, will not be content to return to a crammed phone with a multi-tap dial pad. The explosion in the number of BlackBerry devices has raised peoples’ expectations, and also created a tempting marketplace for programmers everywhere. BlackBerry applications offer a surprisingly rich and expressive interface for a mobile device, and people are willing to pay for the best apps available. People sell their applications on BlackBerry App World, through off-deck stores like Handango, and through wireless carrier stores. Many more people program for fun and load their applications on their own devices or those of friends. And, because BlackBerry still has a dominant presence in the enterprise marketplace, many programmers write applications particularly for their internal business customers. This book will show you how to make the most of your BlackBerry applications. It focuses on the most fun, the most impressive, and the most rewarding aspects of development. By the time you finish, you should be able to write professional-quality applications.